Increased Insulin Like Growth Factor-1 and Antropometri in Premature Infants with Breast Milk - I Dewa Ayu Agung Sridharaswari; Mira Irmawati; Ahmad Suryawan; Irwanto idris; Endang Retnowati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Massage stimulation has consistently led to greater anthropometric in preterm infant by increasing IGF-1 in which plays an important role in promoting growth by stimulating cell growth, multiplication and inhibiting apoptosis. This research to analyze the effect of massage stimulation on IGF-1 and anthropometric in breastfeeding preterm infant. A randomized control trial was conducted on preterm infant with gestational age less than 37 weeks between February – May 2018 in nursery Dr. Soetomo Hospital. Fifty infants in nursery was randomly assigned to massage stimulation or control group. Massage stimulation consisted for three, 15 minutes periods per day for 10 days. Insulin Growth Factor -1 serum was examined on day 1 and 10. Data were analyzed by statistical software using t-test and spearman correlation. The average increase of IGF -1 in massage group was 4.8 (SD 4.41) and 3.1 (SD 3.57) in control group. The average increase of body weight was 252.2 (SD 208.55) in massage group, and 137.9 (SD 69.78) in control group. The average increase of body length was 2 (0.68) in massage group, and 1.1 (0.33) in control group. The average increase of head circumference was 1.5 (SD 0.82) in massage group, and 0.9 (0.28) in control group. The positive correlation between the mean increase of IGF-1 and body length was 0.347. The conclusion was IGF-1 and anthropometric increase in both groups, but the massage group has a significantly higher mean. An increase in IGF-1 correlates with increase in body length.